2019
DOI: 10.1038/s41467-019-13364-2
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloid lineage enhancers drive oncogene synergy in CEBPA/CSF3R mutant acute myeloid leukemia

Abstract: Acute Myeloid Leukemia (AML) develops due to the acquisition of mutations from multiple functional classes. Here, we demonstrate that activating mutations in the granulocyte colony stimulating factor receptor (CSF3R), cooperate with loss of function mutations in the transcription factor CEBPA to promote acute leukemia development. The interaction between these distinct classes of mutations occurs at the level of myeloid lineage enhancers where mutant CEBPA prevents activation of a subset of differentiation ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…These findings are similar to Su and colleague's findings regarding CSF3R in adult bi CEBPA AML 42 . Though these CSF3R mutations alone promote the proliferation and differentiation of neutrophil precursors (ie, the CNL phenotype), CEBPA mutations block the differentiation signal downstream of CSF3R while preserving its proliferative effects, resulting in clonal expansion of immature myeloid cells and the AML phenotype 59‐61 . Distinct from adult AML, Hollink and colleagues found that FLT3‐ITD mutations occurred with similar frequency in both mo CEBPA and bi CEBPA childhood AML, and these mutations had no effect on OS or EFS 9 .…”
Section: Cebpa‐mutant Aml In Pediatric Populationssupporting
confidence: 75%
See 1 more Smart Citation
“…These findings are similar to Su and colleague's findings regarding CSF3R in adult bi CEBPA AML 42 . Though these CSF3R mutations alone promote the proliferation and differentiation of neutrophil precursors (ie, the CNL phenotype), CEBPA mutations block the differentiation signal downstream of CSF3R while preserving its proliferative effects, resulting in clonal expansion of immature myeloid cells and the AML phenotype 59‐61 . Distinct from adult AML, Hollink and colleagues found that FLT3‐ITD mutations occurred with similar frequency in both mo CEBPA and bi CEBPA childhood AML, and these mutations had no effect on OS or EFS 9 .…”
Section: Cebpa‐mutant Aml In Pediatric Populationssupporting
confidence: 75%
“…42 Though these CSF3R mutations alone promote the proliferation and differentiation of neutrophil precursors (ie, the CNL phenotype), CEBPA mutations block the differentiation signal downstream of CSF3R while preserving its proliferative effects, resulting in clonal expansion of immature myeloid cells and the AML phenotype. [59][60][61] Distinct from adult AML, Hollink and colleagues found that FLT3-ITD mutations occurred with similar frequency in both moCEBPA and biCEBPA childhood AML, and these mutations had no effect on OS or EFS. 9 Tarlock and colleagues' bZIP study similarly found no differences in rates of FLT3-ITD or NPM1 mutations between moCEBPA and biCEBPA AML patients, but the prognostic effect of either mutation was not examined.…”
Section: Ceb Pa-mutant Aml In Ped Iatri C P Opul Ationsmentioning
confidence: 99%
“…Recently, a direct co-occurrence between CEBPA and granulocyte colony-stimulating factor receptor (CSF3R) mutations has been reported [134,135]. Notably, near 30% of patients with CEBPA biallelic mutations feature a CSF3R mutation; in these patients the co-occurrence induces a worsening outcome [136,137].…”
Section: Cebpa Mutationsmentioning
confidence: 99%
“…We further identified two mutated genes (CSF3R and KMT2A) and a genetic group (DNA methylation) which conferred prognostic significance in our cohort. Braun et al (30) confirmed that CEBPA mutations must be the initial event prior to mutant CSF3R since otherwise, AML did not develop and CSF3R and CEBPA mutations cooperated to promote leukemogenesis. CSF3R, which is involved in the JAK-STAT signaling pathway, is a common tyrosine kinase mutated gene in biCEBPA mutated AML patients who were sensitive to JAK inhibition (9,11,31).…”
Section: Discussionmentioning
confidence: 99%